Toricones: burst pressures - Ifayefunmi, Olawale; Blachut, Jan (2014)
The paper describes burst pressures of eight mild steel toriconical shells of laboratory scale. This is both a theoretical (numerical) and experimental study. All test models were initially loaded by external pressure until they buckled/collapsed. The toricones were subsequently internally pressurised until burst. The details about the numerical process which simulates the two-stage loading profile, i.e., starting with buckling by external pressure being followed by re-loading using internal pressure for up to the burst, are given. The paper concentrates on numerical procedure which allows computation of the burst pressure using extensive plastic straining as a possible superior approach. It is argued that burst pressure based on the excessive plastic straining is closer to reality than the alternative approach based on plastic instability. The ratio of experimental burst pressure to the finite element computed values was found to be [(1.35, 0.96),(0.89, 0.92), (0.93, 0.90), (1.07, 0.95)] for four nominally identical pairs, respectively. Alternative approach to the estimation of burst pressure, based on plastic instability, gives the above ratio as [(0.79, 0.83), (0.77, 0.76), (0.74, 0.74), (0.74, 0.75)]. Hence the plastic instability based burst significantly, and consistently, overestimated experimental values. The proposed algorithm gave safe predictions for two cases (1.35, 1.07) and in the remaining six the predictions were on unsafe side (0.96, 0.89, 0.92, 0.93, 0.90, 0.95) but the disparity was not as bad as for the plastic instability approach.